The complete chloroplast genome sequence of rose-gold pussy willow, Salix gracilistyla Miq. (Salicaceae) - Xi, Hong (Mitochondrial DNA B Resour, 2019)
To understand genetic background of Salix gracilistyla Miq., we presented its complete chloroplast genome which is 155,557 bp and has four sub regions: 84,530 bp of large single copy (LSC) and 16,218 bp of small single copy (SSC) regions are separated by 27,405 bp of inverted repeat (IR) regions including 130 genes (84 protein-coding gene, eight rRNAs, and 38 tRNAs). The overall GC content of the chloroplast genome is 36.7% and those in the LSC, SSC, and IR regions are 34.5%, 31.0%, and 41.9%, respectively. Phylogenetic trees show phylogenetic position of S. gracilistyla with low level of inter-species sequence variations.